Implementasi Program Rehabilitasi Sosial bagi Pengemis oleh Dinas Sosial Kota Palangka Raya: Implementation of Social Rehabilitation Program for Beggar by Social Services of Palangka Raya City - Fitriani, Fitriani; Sari, Mita; Arafat, Arafat (Anterior Jurnal, 2025)
The problem of beggars in Palangka Raya City is one of the complex social issues, reflecting social inequality and the failure of an inclusive social protection system. This study uses a qualitative descriptive approach to analyze the implementation of the social rehabilitation program run by the Palangka Raya City Social Service to deal with beggars. This study collected data through interviews, observations, and documentation from various informants, including Social Service employees, social assistants, and beggars who had participated in the program. The study results indicate that the social rehabilitation program, which includes data collection, mental coaching, skills training, and social assistance, still faces various obstacles. The main challenges are low participation of beggars, limited rehabilitation facilities, a limited number of social assistants, and difficulties in social reintegration. In addition, the skills training provided is not fully practical due to limited job opportunities and post-rehabilitation support. However, some beggars have successfully undergone rehabilitation and live independently. This study recommends improvements in the capacity of rehabilitation facilities, the number of social assistants, a more holistic approach, and stronger economic empowerment to increase the program's effectiveness. It is hoped that with these steps, the social rehabilitation program can significantly impact beggars in Palangka Raya City.